Arab free zones and their impact on the host country’s development - Alzyoud, Abdullah Suliman Oqla (Journal of Economic, Administrative and Legal Sciences, 2021)
Free zones are considered one of the most important means of economic openness, which countries have sought to establish and work to provide factors for their success. They are based on liberating the economy from restrictions and obstacles, attracting foreign national investments, and providing facilities, incentives and encouraging investment advantages, and it helps to overcome the obstacle of narrow local markets, and push forward the economic development of the host country, by providing job opportunities, reducing unemployment and increasing national income, and most countries of the world understood the importance of free zones and sought to increase their number and establish them in various regions, and the host countries must create a suitable environment for investment in all economic, legislative, political and administrative aspects, and work to remove all obstacles and barriers that hinder the investment process in the free zones.